Great and small military events in Roman archaeology: two case studies of Battlefield Archaeology in comparison (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2023)
Battlefield Archaeology adopts a methodology that is specific to the study of military sites. Concerning ancient battlefields, the distinction between great military events, narrated in written sources, and minor events, which are not recorded, must also be taken into account while setting the research. One of the problems of this discipline is the difficulty of applying to ancient battlefields the method born in the Eighties to study modern ones. Recently, some sites have offered the opportunity to experiment with the construction of a more suitable method for ancient battlefields: this paper analyzes two Roman sites, Pedrosillo and Baecula, chosen for their similarity and for having originated respectively from a small and a great event. The methodologies adopted and results obtained are then compared. The aim is to understand to what extent the distinction between great and small events affects the approach to research and to what extent, in turn, this impacts the nature of the results.
Keywords: Battlefield Archaeology; Baecula; Pedrosillo; methodology; written sources; Roman military archaeology